Ethical Leadership Practices and Staff Organizational Commitment: The Mediating Role of Job Satisfaction in Public Universities of Eastern Ethiopia - Kidane, Befekadu Zeleke; Hundessa , Feyera Dinsa; Afework, Tadesse Hailu; Mekonnen, Guyasa Desalegn (Journal of Interdisciplinary Studies in Education, 2026)
The objective of this study was to investigate the status of ethical leadership practices and their impact on academic staff organizational commitment. A survey design was employed in this study. A sample size of 351 academic staff and 242 university leaders was selected. The Ethical Leadership Survey, the Minnesota Satisfaction Questionnaire, and three commitment models were used to collect data. Both descriptive and inferential data analyses were conducted. The study revealed notable differences in perceptions between university leaders and academic staff about ethical leadership practices. The study revealed that Ethical leadership predicts the organizational commitment of academic staff. Job satisfaction partially mediates the relationship between ethical leadership and academic staff affective commitment. However, it fully mediates between ethical leadership, continuance commitment, and normative commitment.